Online Social anxiety Cognitive therapy for Adolescents (OSCA): protocol for a randomised controlled trial - Eleanor Leigh; David M. Clark (Trials, 2019)
Abstract Background Adolescent social anxiety disorder (SAD) is common, impairing and persistent. There is a need to intervene early to avert its long-term consequences. Cognitive Therapy for SAD is the leading treatment for adults and shows promise for adolescents. However, given the scale of the problem of adolescent SAD and the limited availability of psychological therapists in child and adolescent mental health services, there is a substantial gap in service provision. Delivering therapy via the Internet may provide part of the solution to this problem. An Internet version of adult Cognitive Therapy for SAD has been developed, with outcomes similar to face-to-face therapy. We have recently adapted this treatment for use with adolescents with SAD. Here, we describe a randomised controlled trial designed to test the efficacy of Internet Cognitive Therapy for adolescent SAD compared to waitlist. Methods/design Forty adolescents aged 14–18 years with a diagnosis of SAD will be recruited via schools. Participants will be randomly allocated to Internet Cognitive Therapy or to waitlist. All participants will be assessed three times during the study—at baseline (pretreatment/wait), midtreatment/wait (week 8) and posttreatment/wait (week 15). Participants in the experimental arm will also complete weekly measures as part of the online program and they will be assessed at 3 and 6 months. Postwait, participants in the waitlist arm will be offered Internet Cognitive Therapy, and weekly and posttreatment data will also be collected for them. The trial aims to test whether Internet Cognitive Therapy is superior to waitlist in reducing social anxiety symptoms and in reducing the proportion of adolescents meeting criteria for SAD. Other outcomes of interest include depression and general anxiety symptoms. Acceptability of the online treatment will also be evaluated. Discussion This randomised controlled trial will provide preliminary evidence on whether this intervention, requiring relatively low levels of therapist input, is safe and clinically effective. If this is shown to be the case, Internet Cognitive Therapy for adolescents has the potential to provide a service to the large population of adolescents with untreated SAD. Trial registration ISRCTN Registry, ISRCTN15079139. Version 1 registered on 06/02/2019.